Dietary phytochemical index and overweight/obesity in children: a cross-sectional study - Omid Eslami; Mahdi Khoshgoo; Farzad Shidfar (BMC Research Notes, 2020)
Abstract Objective The aim of the present study was to examine the relationship between the dietary phytochemical index (DPI) and overweight/obesity in children. This cross-sectional study was comprised of 356 children aged 7 to 10 years-old study in the city of Tehran, Iran. The dietary intake of participants was collected using a validated food frequency questionnaire. The DPI was calculated based on the daily energy derived from phytochemical-rich foods. The definition of overweight and obesity was based on the criteria developed by the US Chronic Disease Center for prevention and health promotion. Results The overall prevalence of overweight/obesity was 35.1%. The mean (standard deviation) of the DPI was 14.25 (4.13), 24.12 (2.64), 35.41 (3.62) and 61.52 (16.47) in the first, second, third and fourth quartiles (Q), respectively. Subjects in the higher quartiles of DPI had a significantly higher intake of dietary fiber, vitamin C, and potassium compared to those in the lower quartiles. In the multiple regression analysis, subjects in the highest quartile of DPI had significantly lower odds of being overweight/obese compared to those in the first quartile [odds ratio and 95% confidence intervals for Q4 vs. Q1: 0.47 (0.25, 0.87); P for trend = 0.02].